The role of family support in maternal mental health during the postpartum period in Malaka District - Atok, Yosefa Sarlince; Sormin, Roslin E. M.; Babis, Isna Yuswela (Alma Ata University Press, 2025)
Background: Postpartum depression is a major maternal mental health concern that remains insufficiently addressed in rural areas such as Malaka District, East Nusa Tenggara, where structural and social vulnerabilities may heighten psychological risks. Limited evidence from these settings underscores the need to understand the contextual determinants influencing maternal mental health. Objectives: The objective of this study was to examine the relationship between family support, sociodemographic characteristics, and the risk of postpartum depression among mothers in Malaka District.Methods: This cross-sectional analytic study involved 100 postpartum mothers selected through purposive sampling. Data were collected using a structured questionnaire that included demographic characteristics, a family support scale, and the Edinburgh Postnatal Depression Scale (EPDS). Statistical analyses comprised descriptive tests, chi-square tests, and multivariate logistic regression. Results: The results indicated that 40% of participants were at risk of postpartum depression (EPDS ≥13), and more than half (55%) experienced inadequate family support. Bivariate analysis revealed a significant association between family support and postpartum depression (p=0.001). Multivariate logistic regression demonstrated that inadequate family support was the strongest predictor of postpartum depression, with affected mothers having 3.8 times higher odds of developing depression (AOR 3.8; 95% CI: 1.7–8.3). Low maternal education was also a significant predictor (AOR 2.5; 95% CI: 1.1–5.8), whereas maternal age and employment status were not associated with depression risk. Conclusions: These findings emphasize the critical role of family involvement and maternal education in mitigating postpartum mental health problems. Strengthening the active participation of husbands and family members, improving maternal mental health literacy, and integrating family-centered approaches into antenatal and postnatal care are essential steps for reducing the burden of postpartum depression in Malaka District.